2021
DOI: 10.1108/jhr-01-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Transtheoretical model on the self-care behavior of hypertension patients: a systematic review

Abstract: PurposeThis review aims to describe the effectiveness of education with the transtheoretical model (TTM)-based on the self-care behavior of hypertension patients.Design/methodology/approachA systematic literature search was carried out on four databases: PubMed, Science Direct, Cochrane and Grey literature to identify studies reported in English which were published in the last ten years. The literature search was conducted from November 13 to December 10, 2020.FindingsBased on the six studies that have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This findings ;was supported by; [10] .They reported that, According to model-based education, behavioral changes in hypertensive patients affect significant reductions in blood pressure. Blood pressure changes with a decrease in systolic and diastolic blood pressure in more than half of the samples, after application of Trans theoretical model.…”
Section: Discussionmentioning
confidence: 72%
“…This findings ;was supported by; [10] .They reported that, According to model-based education, behavioral changes in hypertensive patients affect significant reductions in blood pressure. Blood pressure changes with a decrease in systolic and diastolic blood pressure in more than half of the samples, after application of Trans theoretical model.…”
Section: Discussionmentioning
confidence: 72%
“…A systematic review suggested using the TTM for digital interventions as it is effective in promoting behaviour change. 56 The TTM is appropriate for use in this study because it specifies the mediators to be used at each stage of change. Since the patients in this study are at different stages of readiness for change, the TTM model was the most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the total number of participants in the study was determined to be 114 individuals. A tailored behavior intervention, with a minimum duration of six months, was identified as the most appropriate approach [ 21 ]. Following a 6-month follow-up period, two women from the intervention group were excluded from the study due to pregnancy.…”
Section: Methodsmentioning
confidence: 99%